HUBUNGAN ANTARA RELIGIOSITAS DENGAN AGRESIVITAS PADA KOMUNITAS PEMUDA GEREJA - Wijaya, Eirena Fiola; Aditya, Yonathan; Matahari, David (Jurnal Psikologi Ulayat: Indonesian Journal of Indigenous Psychology, 2018)
Abstract — A lot of individuals have lived their lives with a strong attachment towards religion; however some of them still have a high aggressive behavior. This phenomenon is also evident in the youth communities within the church. The core teaching of the Christianity is love, in which love is supposed to inhibit individuals to initiate aggressive behavior. This study aims to explore the correlation between religiosity, which has two components (intrinsic religiosity orientation and extrinsic religiosity orientation), towards aggressive behavior in youth communities within the church. This study used quantitative method. To obtain and collect the data, we used the aid of questionnaire distributed through purposive technique towards 87 subjects. The instruments included the Verbal Aggressive Scale for the aggressive behavior, the I/E-R Scales to measure religious orientation, and Faith Development Scale to measure the development of faith in each individual. The result of this research pointed out that there is no significant correlation between intrinsic religious orientation and aggressive behavior and that is a positive correlation between extrinsic religious orientation and aggressive behavior.Abstrak — Banyak individu yang memiliki hidup dengan keterkaitan yang erat dengan agama, namun di sisi lain perilaku agresivitas mereka tetap tinggi. Fenomena ini juga terjadi dalam komunitas pemuda gereja. Inti dari ajaran agama Kristen adalah kasih, di mana idealnya kasih tersebut menahan individu untuk tidak melakukan perilaku agresif. Untuk menjelaskan fenomena ini, dilakukan penelitian mengenai hubungan antara religiositas, yang di dalamnya terdiri dari orientasi religiositas intrinsik dan ekstrinsik, dengan agresivitas pada pemuda gereja. Penelitian ini menggunakan metode kuantitatif. Pengumpulan data dilakukan dengan kuesioner di mana sampel diambil dengan teknik purposive sampling kepada 87 responden. Alat ukur yang digunakan dalam penelitian ini adalah Verbal Aggressiveness Scale untuk mengukur agresivitas, I/E-R Scales untuk mengukur orientasi religiositas, dan Faith Developmental Scale untuk mengukur perkembangan iman. Hasil penelitian menunjukkan tidak adanya korelasi yang signifikan antara religiositas intrinsik dengan agresivitas, namun terdapatnya korelasi positif antara religiositas ekstrinsik dengan agresivitas.